Editorial Commentary: Hip Primary Labral Repair Versus Reconstruction: Equally Successful Outcomes Can Be Achieved Based on Proper Indications - Harris, Joshua D (Arthroscopy, 2022)
One of the core principles of hip arthroscopy is preservation of the acetabular labrum. Compromise of the biomechanical function of the labrum underlies a significant symptom source in patients undergoing hip preservation surgery. As surgical techniques continue to improve and evolve beyond labral repair, increased use of advanced arthroscopic procedures like segmental and circumferential reconstruction shed further light on the optimal labral intervention. In the revision setting, labral deficiency warrants labral reconstruction or augmentation. Both segmental and circumferential techniques may significantly improve patient-reported outcomes. However, in the primary setting, controversy exists not necessarily in the surgical technique, but more in the indications to perform which specific labral intervention. Reasonable indications for primary labral reconstruction include a calcified or ossified labrum, irreparable labral tissue, and hypotrophy of the labrum (less than 2-3 mm) with a proven deficient suction seal without resistance to axial distraction. Short-term multicenter studies demonstrate similar success rates between primary labral reconstruction and repair using validated patient-report outcome scores. Mid- and long-term clinical and economic investigations comparing labral reconstruction and repair are needed to determine the role of primary reconstruction in modern arthroscopic hip preservation surgery.